Some immunological parameters in Hodgkin's disease - Dienstbier, Z; Hermanská, Z; Pĕnicka, P; Zámecník, J (Neoplasma, 1988)
Mononuclear cells in the peripheral blood of 69 previously untreated patients with Hodgkin's disease were investigated and their changes were followed up in the course of the disease. Before the initiation of the treatment, the total number of lymphocytes, cells with ring-shaped nucleolus, E-rosette forming cells and lymphocytes with dot-like ANAE positivity were decreased and ferritin-bearing lymphocytes significantly highly increased (p less than 0.01) when compared with healthy persons. In cells of the monocyte-macrophage lineage, only the total number of cells in initial state of transformation to macrophages (active nucleolus) was significantly highly increased (p less than 0.05). In comparison with early stages, only the changes of quiet, resting cells were significantly more pronounced in advanced disease (p less than 0.01 and p less than 0.05). An excessive depression of ring-shaped nucleolus-bearing cells was associated with B symptoms. Using a discriminant analysis method, the independent influence of these cells upon the immunocompetence of the patients has been proved. After the completion of primary treatment the changes of cells were more profoundly expressed. No complete restauration of immunocompetence has been found within 1-2 years in patients responding satisfactorily to therapy. Verified by the discriminant analysis, persistent imbalance of T-lymphocyte subpopulations plays the most important role in the immune defect of patients in the second year after the therapy and later.
Keywords: Immunity, Cellular; Lymphocytes; Humans; počet leukocytů; lidé; Leukocyte Count; Monocytes; buněčná imunita; lymfocyty; monocyty; Hodgkin Disease; Hodgkinova nemoc